Rice MutLγ, the MLH1–MLH3 heterodimer, participates in the formation of type I crossovers and regulation of embryo sac fertility. Issue 7 (22nd February 2021) - Mao, Bigang; Zheng, Wenjie; Huang, Zhen; Peng, Yan; Shao, Ye; Liu, Citao; Tang, Li; Hu, Yuanyi; Li, Yaokui; Hu, Liming; Zhang, Dan; Yuan, Zhicheng; et al.
Summary: The development of embryo sacs is crucial for seed production in plants, but the genetic basis regulating the meiotic crossover formation in the macrospore and microspore mother cells remains largely unclear. Here, we report the characterization of a spontaneous rice female sterile variation 1 mutant ( fsv1 ) that showed severe embryo sacs abortion with low seed‐setting rate. Through map‐based cloning and functional analyses, we isolated the causal gene of fsv1, OsMLH3 encoding a MutL‐homolog 3 protein, an ortholog of HvMLH3 in barley and AtMLH3 in Arabidopsis . OsMLH3 and OsMLH1 (MutL‐homolog 1) interact to form a heterodimer (MutLγ) to promote crossover formation in the macrospore and microspore mother cells and development of functional megaspore during meiosis, defective OsMLH3 or OsMLH1 in fsv1 and CRISPR/Cas9‐based knockout lines results in reduced type I crossover and bivalent frequency. The fsv1 and OsMLH3 ‐knockout lines are valuable germplasms for development of female sterile restorer lines for mechanized seed production of hybrid rice.